Mobilising Expertise and Resources to Close the Radiotherapy Gap in Cancer Care. Issue 2 (February 2017) - Rodin, D.; Longo, J.; Sherertz, T.; Shah, M.M.; Balagun, O.; Wendling, N.; Van Dyk, J.; Coleman, C.N.; Xu, M.J.; Grover, S.
Abstract: Closing the gap in cancer care within low- and middle-income countries and in indigenous and geographically isolated populations in high-income countries requires investment and innovation. This is particularly true for radiotherapy, for which the global disparity is one of the largest in healthcare today. New models and paradigms and non-traditional collaborations have been proposed to improve global equity in cancer control. We describe recent initiatives from within the radiation oncology community to increase access to treatment, build the low- and middle-income countries' radiation oncology workforce, mobilise more professionals from within high-income countries and raise awareness of the global need for equitable cancer care.